Effect of Zn2+ ions on the assembly of amylin oligomers: insight into the molecular mechanisms. Issue 31 (18th July 2016) - Wineman-Fisher, Vered; Miller, Yifat
Abstract : High and low concentrations of Zn 2+ ions decrease the polymorphism of amylin oligomers and do not affect their cross β-beta structures. Abstract : Amylin is an endocrine hormone and is a member of the family of amyloid peptides and proteins that emerge as potential scaffolds by self-assembly processes. Zn 2+ ions can bind to amylin peptides to form self-assembled Zn 2+ –amylin oligomers. In the current work the binding sites of Zn 2+ ions in the self-assembled amylin oligomers at various concentrations of zinc have been investigated. Our results yield two conclusions. First, in the absence of Zn 2+ ions polymorphic states ( i.e. various classes of amylin oligomers) are obtained, but when Zn 2+ ions bind to amylin peptides to form Zn 2+ –amylin oligomers, the polymorphism is decreased, i.e. Zn 2+ ions bind only to specific classes of amylin. At low concentrations of Zn 2+ ions the polymorphism is smaller than at high concentrations. Second, the structural features of the self-assembled amylin oligomers are not affected by the presence of Zn 2+ ions. This study proposes new molecular mechanisms of the self-assembly of Zn 2+ –amylin oligomers.